Implementation of orthogonal frequency division multiplexing for software defined radio - Guevara, Maria Katrina D. (2011)
Software Defined Radio (SDR) is a rapidly evolving radio technology that can support multiple communication standards and systems. It is configured by modifiable software operating on reprogrammable hardware, thus giving the advantages of flexibility and adaptability. With the emergence of wireless communication technology and increase in number of wireless device users, bandwidth has become even more in demand. Orthogonal Frequency Division Multiplexing (OFDM) for SDR offers better bandwidth utilization and is the popular choice for wireless communication systems. This project is an implementation of an SDR that uses OFDM on an XtremeDSP development platform. The transmitter and receiver were modeled and simulated using the Xilinx blockset in MATLAB Simulink then implemented on hardware using Xilink System Generator. System parameters such as number of subcarriers and modulation scheme were varied for speech and audio inputs. Performance of the SDR system was evaluated by measuring bit error rate, peak-to-average power ratio and spectral efficiency under simulated channel conditions with signal-to-noise ratios of 15 and 20 db. The tradeoffs among these were examined in the SDR. BER and spectral efficiency increase with M-ary modulation. PAPR increases with M-ASK but remains constant for M-PSK. BER decreases, spectral efficiency decreases and PAPR increases as the number of subcarriers increases. For speech inputs, 8-FFT 16-ASK and 16-FFT 64-ASK are acceptable for SNR of 15 and 20 db, respectively. For audio inputs, 8-FFT 8-PSK and 8-FFT 16-ASK are acceptable. These were based on a minimum BER of 10-2 for speech and 10-3 for audio inputs. The chosen configurations were implemented on a Xilinx Virtex-5 XC5VSX50TFFG1136 FPGA build in the XtremeDSP Development Platform ML506 Edition using JTAG hardware co-simulation. The BER performance of the system on hardware was consistend with that observed in simulations using fixed-point computations.